Tradisi Adat Kawi’a Masyarakat Suku Moronene Di Kecamatan Poleang Utara Kabupaten Bombana - Anwar Anwar; Amal Arfan; Erman Syarif (Universitas Negeri Makassar, 2019)
The study aims at (1) examining the proses of Kawi’a traditional tradition or marriage of Moronene tribe in North Poleang subdistrict in Bombana district, (2) the role of Tolea in Kawi’a traditional tradition of marriage of Moronene Tribe in North Poleang Subdsitrict in Bombana district, and (3) integrating the Kawia’a traditional tradition or marriage in Geography learning material in SMA (senior high school). This study employed qualitative research with ethnography approach. The data source of the study employed snowball sampling technique with the informants consisted of customary council chairman of Moronene, Tolea, and prominent people. Data Collecting technique employed direct observation, in-depth interview, and documentation. Data analysis technique consisted of data collecting, data reduction, data display, and conclusion drawing. The results of the study reveal that (1) the process in Kawi’a tarditional tradition or marriage of Moronene tribe in North Poleang subdistrict in Bombana district is divided into three stages, namely pre-marriage stage which consist of Mowindahako (marriage proposal), Moduduhi, Mompokontodo (following the marriage proposal), Mesisiwi (persuading the bride), Mesampora (engagement), Lumanga (delivery the dowry) and Khatam Qur’an. The marriage stage consists of Melongko (picking up the bride), Metiwawa (taking the bride to the venue), Melawati/Moantani (welcoming the bride), Mompindai Sincu (confirming the bride and groom), pinokompe’olo (eating together in on plate), Pinokompompanga (eating the sirih pinang together) dan Montente Awu (Molulo together) and the Post-marriage is called Mohuletako Alo (taking the bride to the parent’s in-law home); (2) the roles of Tolea in Kawi’a traditional tradition of marriage of Moronene Tribe in North Poleang Subdsitrict in Bombana district are the marriage proposal carrier, following the marriage proposal, discussing and deciding as well as taking the dowry and marriage cost, conducting the procession before and after the marriage and taking the bride to the parent’s in-law home; (3) the Kawi’a traditional tradition or marriage of Moronene tribe can be integrated in Geography learning material in class XI at SMA inside or outside of the clas in a form of field observatioan and applying character education values caontained in Kawi’a traditional tradition such as being religious, discipline, responsibility and caring working togehter in daily lives in school environment as well as in the society.Tujuan Penelitian ini adalah (1) Untuk mengetahui proses dalam tradisi adat Kawi’a / perkawinan masyarakat Moronene di Kecamatan Poleang Utara Kabupaten Bombana, (2) Untuk mengetahui peran Tolea dalam adat tradisi Kawi’a / perkawinan masyarakat Suku Moronene di Kabupaten Bombana, (3) Untuk mengintegrasikan tradisi adat Kawi’a / Perkawinan dalam materi pembelajaran geografi di SMA. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan etnografi. Sumber data mengggunakan teknik snowball sampling dengan memilih informan yang terdiri dari Ketua Dewan Adat Moronene, Tolea dan Tokoh Masyarakat. Teknik pengumpulan data melalui observasi langsung, wawancara mendalam dan dokumentasi. Teknik analisis data terdiri dari pengumpulan data, reduksi data, display data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa (1) proses dalam tradisi adat kawi’a / perkawinan masyarakat Moronene di Kecamatan Poleang Utara Kabupaten Bombana terbagi dalam tiga tahap yaitu tahap praperkawinan yang terdiri dari Mowindahako (Pelamaran), Moduduhi, Mompokontodo (Menyusul lamaran), Mesisiwi (membujuk Pengantin), Mesampora (Pertunangan), Lumanga (pengantaran Pokok Mahar) dan Khatam Qur’an. Tahap Perkawinan terdiri dari Melongko (Menjemput pengantin), Metiwawa (mengantar pengantin ke tempat acara), Melawati/Moantani (menyambut pengantin), Mompindai Sincu (Mengukuhkan Pengantin), pinokompe’olo (Makan Bersama dalam satu piring), Pinokompompanga (Makan Sirih Pinang Bersama) dan Montente Awu (Molulo Bersama) dan tahap Pascaperkawinan disebut Mohuletako Alo (mengantar Pengantin ke rumah orang tua laki-laki): (2) peran tolea dalam adat tradisi kawi’a / perkawinan masyarakat Suku Moronene di Kabupaten Bombana yaitu pembawa lamaran, menyusul lamaran, membicarakan dan memutuskan serta mengantar Pokok Mahar dan Biaya Perkawinan, melaksanakan prosesi adat sebelum dan sesudah perkawinan dan mengantar pengantin ke rumah orang tua pengantin laki-laki (3) tradisi adat Kawi’a / Perkawinan masyarakat suku moronene dapat dintegrasikan dalam materi pembelajaran geografi kelas XI (Sebelas) di SMA baik di dalam maupun di luar kelas dalam bentuk observasi lapangan dan menerapkan nilai-nilai pendidikan karakter yang ada dalam tradisi adat Kawi’a tersebut seperti Religius, Disiplin, Tanggung Jawab dan Peduli Sosial / Gotong Royong dalam kehidupan sehari-hari baik di lingkungan sekolah maupun di lingkungan masyarakat.